Dr. Marcin Jadczak — Deep Plane Facelift — Warsaw - Jadczak, Marcin (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Marcin Jadczak, practicing in Warsaw, Poland. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003253; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; poland; warsaw